The presentation of a consolidated identity in "100 Years of Visual Arts at the Arts Institute at UFRGS: Three Essays" - Silveira, Paulo (PORTO ARTE: Revista de Artes Visuais, 2016)
Review on the commemorative volume "100 anos de artes plásticas no Instituto de Artes da UFRGS: três ensaios" [100 Years of Fine Arts at the Arts Institute at UFRGS: Three Essays], published by Editora da UFRGS in 2012 (264 pages, ISBN 978-85-386-180-7), written by professors Blanca Brites, Icleia Borsa Cattani, Maria Amélia Bulhões and Paulo Gomes